Interaction on factors that influencing demand of foreign worker hospitalization and surgical scheme / Khairunnisa’ Yussof - Yussof, Khairunnisa’ (Faculty of Business and Management, 2011)
This research is about the factors that influencing demand of Foreign Worker Hospitalization and Surgical Scheme. The independent variable such as Legislation, Reduce Financial Burden of Employer, Types of Work or Business and Intermediaries are being identified in order to make an investigated whether or not these independent have significant and influenced the demand of the scheme. This research was conducted in Damansara Height, Kuala Lumpur where 50 questionnaires were distributed and 50 questionnaires were returned. In order to obtain the data, the researcher was used two methods that are primary and secondary data. Data analyzed using reliability test, frequency analysis, Pearson correlation analysis and regression analysis. Based on the analysis, the result shows that the most influence factor that associated with demand of Foreign Worker Hospitalization and Surgical Scheme was Legislation.